Analisis Penyebab Rendahnya Minat Literasi Siswa Kelas II SDN Simolawang KIP/156 - Ulfa, Siti Madiah; Sholikhah, Saosa Yumrotus (Lembaga Yasin AlSys, 2025)
The low literacy level among the Indonesian population, which limits students' knowledge and insight, serves as the background for this study, which specifically aims to analyze the causes of low literacy interest among second-grade students at SDN Simolawang KIP/156. This study employed a qualitative descriptive method with all second-grade students as subjects, observed directly based on manifestations of their literacy interest. Data were collected through interviews and observations, then analyzed using thematic analysis techniques. The findings reveal that laziness, lack of parental support, and unsupportive economic conditions are the main inhibiting factors for students’ literacy interest. These findings reinforce previous studies, such as Ramadhani et al. (2025), regarding the impact of reading interest on students’ reading comprehension. The main conclusion indicates that low literacy interest results from the interaction between internal student factors and external factors from the social environment. The implications of this study include theoretical contributions to the literature on early childhood literacy, as well as practical recommendations for educational institutions to design more contextual, comprehensive, and responsive literacy programs tailored to students’ backgrounds. This study also opens opportunities for further exploration in various regions to gain a comparative understanding of the dynamics of students’ literacy interest.